Stratospheric Envelopes for an Atmospheric Mode of Address. Issue 2 (3rd July 2017) - McCormack, Derek P.
Abstract : This article explores the modes of atmospheric address emerging from experiments within the stratosphere. To do so, it draws on archival material associated with Commander Malcolm D. Ross who, during the 1950s and early 1960s, spent more time than any other person in the stratosphere. Coupling accounts of Ross's experimental ascents with his interest in creative writing and communication, this article uses three unopened envelopes carried by Ross into the stratosphere as a point of departure for layering together three strands of thinking. The first is a consideration of the stratosphere as a zone of exchange, experiment, and experience. The second is a reflection on the envelope as a spatiotemporal form, a limit, and a lure for thinking. The third is a discussion of the modes of atmospheric sensing made possible by stratospheric flights. These strands are worked together to develop a distinctive speculative mode of atmospheric address. Such modes of address can contribute to wider efforts across the geohumanities to account for the differentiated materiality and movement of the earth's atmosphere.